Case study on collection development policy, procedures, and collection evaluation of Arabic language collection in IIUM Academic Library - Ruhill Fahima binti Mohammad (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2010)
This study has been conducted in order to ascertain collection development policy, procedures, and collection evaluation of Arabic language collection in IIUM academic library as well as the qualification of the library staff in developing Arabic language collection. A series of individual interviews between researcher and subjects has been conducted. Seven respondents have been interviewed consisting of four professional staff and three support staff from IIUM library. An unstructured observation of collection development process in the IIUM library also has been done in its natural setting. The result shows that the collection development policy in the IIUM library does cover Arabic language collection. In developing Arabic language collection, delivery order is widely used in the selection and acquisition process in the IIUM library whereas for the Arabic serial title collection, standing order method is mostly used. The study also found that there are challenges and difficulties while developing Arabic language collection. In terms of collection evaluation, the result indicates that there is no formal evaluation done for Arabic language collection in the IIUM library. For competencies needed by the IIUM library staff in the collection development of Arabic collection, the finding shows that knowledge in Arabic language, skills in IT, and on-the-job training experience are needed by collection development staff. Finally, based on the Evans's collection development model, IIUM library do practice almost all elements in the model on its Arabic language collection.